2002
DOI: 10.1177/004051750207201207
|View full text |Cite
|
Sign up to set email alerts
|

JetRing Spinning and Its Influence on Yarn Hairiness

Abstract: In the production of cotton and polyester JetRing spun yarns, spindle speed, air pressure, and yarn twist level affect yam hairiness. However, the distance between the front roller nip and the nozzle inlet has only a marginal effect on yam hairiness. Results also show that JetRing spun yams have a much lower numbers of hairs than the equivalent ring spun yams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 10 publications
3
51
0
Order By: Relevance
“…However, based on simulation, they claimed that the rational level of axial angle of air inlets should be in the range 40-50°, as a larger angle caused a longer air recirculation zone causing fiber curving, which according to the authors hindered wrapping of the hairs over the yarn, thereby affecting reduction in hairiness of yarns. 1 Studies based on airflow simulation and experimental work on Nozzle-Ring spinning and Nozzle-Winding conducted by the present authors have shown that air inlets Abstract In this paper we report on computational fluid dynamics (CFD) simulation of airflow inside the nozzles used in Nozzle-Ring spinning. Using the CFD, air velocities at different locations of the nozzle were obtained and then drag forces acting on hair and yarn were computed.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…However, based on simulation, they claimed that the rational level of axial angle of air inlets should be in the range 40-50°, as a larger angle caused a longer air recirculation zone causing fiber curving, which according to the authors hindered wrapping of the hairs over the yarn, thereby affecting reduction in hairiness of yarns. 1 Studies based on airflow simulation and experimental work on Nozzle-Ring spinning and Nozzle-Winding conducted by the present authors have shown that air inlets Abstract In this paper we report on computational fluid dynamics (CFD) simulation of airflow inside the nozzles used in Nozzle-Ring spinning. Using the CFD, air velocities at different locations of the nozzle were obtained and then drag forces acting on hair and yarn were computed.…”
mentioning
confidence: 94%
“…Singeing of yarns, yarn folding, and compact spinning are the ways to control yarn hairiness. The hairiness of yarns can also be controlled by placing an air-nozzle at winding machine or at ring frame [1][2][3][4][5][6][7][8][9][10][11], the latter is termed 'JetRing' and 'Nozzle-Ring spinning'. Zeng and Yu [11] studied air nozzles in ring spinning and winding to reduce yarn hairiness.…”
mentioning
confidence: 99%
“…Equation (11) indicates that a short grooved surface placed in a longer position generates more rollings of the siro-spinning strand to wrap more hairs (illustrated in Figures 3(f)-(h)). Equations (12) and (13) suggest the longer positioned short grooved surface can conduct tighter trapping of hairs by wrapping them onto a more compact siro spun yarn stem (Figure 3(h)).…”
Section: Xia Et Almentioning
confidence: 99%
“…9 Although jet-ring spinning can reduce spun yarn hairiness effectively, 10 it also incurs deterioration of yarn evenness due to the fiber mass concentration in a very short length. 11 To avoid extra energy consumption for the above spinning, re-trappable contact spinning has been used as a simple and energy-saving method to improve yarn smoothness. 12 The dimensions of primary used contact surface devices, such as the plane type 12 and the grooved type, 13 are too large to facilitate installation and operation.…”
mentioning
confidence: 99%
“…The experimental design proposed by Taguchi involves using orthogonal arrays (OAs) to organize the parameters affecting the process and the levels at which they should be varied; it allows the collection of necessary data to determine which factors most affect product quality with a minimum amount of experimentation, thus saving time and resources, (Mavruz & Ogulata, 2007). Studies of the applications of Taguchi design in the textile industry are very new (Cheng & Li, 2002). Taguchi methodology for optimization can be divided into four phases: planning, conducting, analysis, and validation.…”
Section: Introductionmentioning
confidence: 99%